Experience of introduction of the antimicrobial therapy control system in a general hospital - I. V. Shlyk (Вестник анестезиологии и реаниматологии, 2020)
The article is devoted to the issue of control over antibiotic resistance of the main pathogens causing nosocomial infections and presents the experience of introducing the antimicrobial therapy control system in a general hospital. The special emphasis is put on capabilities of information technologies used as a tool to support decision making about prescription or restriction of antibacterial drugs.